Animal andrology [ theories and applications - Chenoweth, Peter J.; Lorton, Steven P. (CABI, 2014)
Understanding animal andrology is fundamental to optimising genetic breeding traits in domestic and wild animals. This book provides extensive coverage of male reproductive biology, discussing the essentials of sperm production, harvest and preservationbefore covering the applications to a range of animals including cattle, horses, pigs, small ruminants, camelids, cats and dogs, poultry and exotic species. It also examines the laboratory procedures that provide the basis of general fertility research.